Negotiating humanity: an ethnography of cadaver-based simulation - MacLeod, Anna; Cameron, Paula; Luong, Victoria; Kovacs, George; Patrick, Lucy; Fredeen, Molly; Kits, Olga; Tummons, Jonathan (Advances in Health Sciences Education, 2023)
Human body donation (HBD) serves an essential function in many medical schools, particularly in institutions where people engage in cadaver-based simulation (CBS) as a pedagogical approach. The people who facilitate HBD and CBS have a highly specialized skill set, yet their expertise remains largely unacknowledged, and takes place out of sight from the broader medical school community. This manuscript, based on a two-year practice-based ethnography (Structured Observations n = 68 h, Unstructured Observations n = 150 + hours; Interviews n = 24; and Document/Policy Analysis n = 14) illuminates the complex work of HBD. We identify three primary functions of HBD and CBS (1. Cadaver Intake & Administration, 2. Cadaver Preparation, and 3. Cadaver-Based Pedagogy). We describe how medical educators involved in CBS have developed a skillset specific to their role: negotiating humanity.
EPrint Processing Status: Full text deposited in DRO